1990
DOI: 10.1007/bf02555041
|View full text |Cite
|
Sign up to set email alerts
|

Sex- and age-related changes in bone and serum osteocalcin

Abstract: We measured bone osteocalcin concentrations in EDTA extracts from iliac crest cortical bone specimens obtained postmortem from 63 men and 71 women (age range 19-90 years), and serum osteocalcin levels in healthy blood donors, 49 men and 49 women (age range 21-65 years). Bone and serum osteocalcin concentrations were higher in men than in women, and an age-related decline was observed in both sexes. In women, however, a temporary increase in serum (P less than 0.05) osteocalcin was seen in the sixth decade. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
32
1

Year Published

1991
1991
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(38 citation statements)
references
References 13 publications
5
32
1
Order By: Relevance
“…Our results are supported by other studies, in which a corresponding increased level of BGP was found before the age of 30 years (25)(26)(27). Furthermore, we found a tendency towards increased fU Ca/Cr in the youngest group, consistent with earlier reports (25).…”
Section: Discussionsupporting
confidence: 95%
“…Our results are supported by other studies, in which a corresponding increased level of BGP was found before the age of 30 years (25)(26)(27). Furthermore, we found a tendency towards increased fU Ca/Cr in the youngest group, consistent with earlier reports (25).…”
Section: Discussionsupporting
confidence: 95%
“…The changes observed after OVX in this study are similar to the changes seen after the menopause in women. Increases in alkaline phosphatase activity, osteocalcin levels [26], and periosteal diameter, and a reduction in 24-hour Ca excretion and bone density are also observed in postmenopausal women [27]. The increased osteocalcin levels observed after OVX reflect a high turnover rate, as demonstrated earlier in ovariectomized dogs [28] and rats [29].…”
Section: Discussionmentioning
confidence: 85%
“…Our results are in agreement with two published studies (33,34) but do not agree with four others. (35)(36)(37)(38) The reasons our correlations of bone markers with E 2 and P differ from those reported in other studies (4,8) are not entirely clear. Those studies did not report whether calculated correlations were from multiple data points per woman or whether they were within woman or between women.…”
Section: Figmentioning
confidence: 79%